Circular economy in Brazil and alignment with the SDGs: Interfaces, gaps and opportunities for future research - Sehnem, Simone; Provensi, Tais; Kuzma, Edson Luiz; Santos, Francielle Mafesoni dos; Godoi, Lucia (Contextus - Revista Contemporânea de Economia e Gestão, 2023)
The objective of this work is to analyze the profile of Brazilian dissertations and theses that deal with circular economy and its alignment with the Sustainable Development Goals (SDGs). A systematic literature review was developed with a portfolio of 96 theses and dissertations published in the Brazilian Digital Library of Theses and Dissertations (BDTD). The results suggest that SDGs 9, 12 and 17 have a closer synergy with the circular economy in the bibliographic portfolio analyzed. Based on the existing gaps for engagement with the other 14 SDGs, a research agenda was prepared with 93 research opportunities and 6 exploratory theoretical propositions for future validation in theoretical-empirical studies.